Small Binary Codebook Design for Image Compression Depending on Rotating Blocks - Hameed, Maha A.; Al-Khoja, Saif B.; Ismail, Rafah Rasheed (Iraqi Journal of Science, 2021)
The searching process using a binary codebook of combined Block Truncation Coding (BTC) method and Vector Quantization (VQ), i.e. a full codebook search for each input image vector to find the best matched code word in the codebook, requires a long time. Therefore, in this paper, after designing a small binary codebook, we adopted a new method by rotating each binary code word in this codebook into 900 to 2700 step 900 directions. Then, we systematized each code word depending on its angle to involve four types of binary code books (i.e. Pour when , Flat when , Vertical when, or Zigzag). The proposed scheme was used for decreasing the time of the coding procedure, with very small distortion per block, by designing small binary codebook, then rotating each block in it. Moreover, it can be used for improving the efficiency of the coding process even further with the decrease in the bit rate (i.e. increasing the compression ratio(.